Tri Hita Karana-Based Environmental Sustainability as a Mediator between Facilities, Value, and Tourist Satisfaction, with Destination Image as a Moderator in Sanur - I Nyoman Angga Darmaputra; Ida Bagus Udayana Putra; Putu Ayu Sita Laksmi (Journal of Governance, Taxation and Auditing, 2026)
This study aims to analyze the mediating role of *Tri Hita Karana*-based environmental sustainability in the relationship between facilities, perceived value, and tourist satisfaction, with destination image acting as a moderator in Sanur Village. An explanatory quantitative approach was employed, utilizing a survey method with questionnaires distributed to 210 tourists visiting Sanur. Purposive sampling was used, and data were analyzed via Structural Equation Modeling-Partial Least Square (SEM-PLS) using SmartPLS 4.0 software. The results indicate that destination facilities have a positive and significant effect on tourist satisfaction, whereas perceived value does not have a significant effect. *Tri Hita Karana*-based environmental sustainability positively and significantly influences tourist satisfaction and mediates the effects of facilities and perceived value on tourist satisfaction. Destination image significantly moderates the relationship between facilities and tourist satisfaction (negatively) and the relationship between perceived value and tourist satisfaction (positively). This study contributes theoretically by integrating the local wisdom of *Tri Hita Karana* into the tourist satisfaction model and offers practical implications for destination managers regarding the development of sustainable, local culture-based tourism.